The Influence Of Career Development And Rewards On Employee Loyalty: A Case Study Of Generation Z Employees At PT Amartha Lampung - Niken Ayu Aprilia; Monica Septiani (Jurnal Ekonomi, 2024)
This study aims to determine the influence of career development and rewards on the loyalty of Generation Z employees at PT Amartha Lampung. Generation Z, which is now starting to enter the workforce, is a major concern for PT Amartha, especially because by 2023, most of the recruited employees are under 25 years old. thus creating new challenges in managing and maintaining their loyalty. The research uses a quantitative method with a statistical approach, utilizing SPSS software. The population in this study consists of employees of PT Amartha Lampung, with a sample size of 120 respondents. The sampling technique used is purposive sampling. Data measurement techniques involve multiple linear regression analysis. The results of the study show that: the partial test results indicate that the T-calculated value for Career Development is 3.654, which is greater than the T-table value of 1.98045, concluding that Career Development has a positive and significant influence on Employee Loyalty at PT Amartha Lampung. The partial test results for Rewards show a T-calculated value of 4.920, which is greater than the T-table value of 1.98045, concluding that Rewards have a positive and significant influence on Employee Loyalty. The simultaneous test results show an F-calculated value of 85.256, which is greater than the F-table value of 3.07, concluding that Career Development and Rewards simultaneously have a positive and significant influence on Employee Loyalty at PT Amartha Lampung.